"Mediate First": The Revival of Mediation in Labour Dispute Resolution in China*. (8th June 2015) - Zhuang, Wenjia; Chen, Feng
Abstract: The past few years have witnessed the revival of mediation as a chief method of labour dispute settlement in China. While the central government's campaign has reinvigorated the use of mediation in order to control social conflicts and maintain stability, its expansion and extensive deployment have also been driven by local authorities, as mediation can better serve their policy priorities and bureaucratic interests. Not only does the extension of mediation provide local bureaucratic agencies with flexibility and discretionary power to resolve conflicts without having to comply with legal minimums, it also legitimizes the courts' "non-legalistic approach" to settling dispute cases. The extensive employment of mediation by local authorities has chipped away at the role of legal procedures in settling labour disputes. The revival of mediation embodies a tension between the rule of law the government has promoted since the reform and the extrajudicial methods it needs for controlling conflicts. 提要: 近年来中国政府开始重新强调将调解作为处置劳动争议的主要方式。虽然中央政府控制社会冲突和维持社会稳定的需要是重振劳动调解的根本原因, 但地方政府因自身施政的权衡和官僚利益的驱动而对调解的偏好, 是导致调解范围扩大和广泛运用的重要因素。劳动调解的广泛运用, 不仅给地方官僚部门化解劳动争议提供了法律程序之外的灵活性和酌情处事权, 甚至也使得法院动用"法外途径"来处置争议案件获得正当性。过度强调"调解优先"蚕食了法律在劳动争议处置过程中的角色。调解的复兴实际上映射出中国政府在改革时期提倡的"依法治国"理念与其依赖法外手段去控制社会冲突的现实需求之间的张力。